Effects of Femoral Rotational Taping on Dynamic Postural Stability in Female Patients With Patellofemoral Pain. Issue 5 (September 2017) - Song, Chen-Yi; Lin, Jiu-Jenq; Chang, Alison H.
Abstract : Objective: To investigate the effects of femoral rotational taping on task performance, dynamic postural control, and pain during the Star Excursion Balance Test (SEBT) in patients with patellofemoral pain (PFP) compared to healthy controls. Design: Case–control study, pretest–posttest. Setting: Laboratory. Participants: Twenty-four female participants (16 with PFP, 8 controls). Interventions: Participants in both the PFP and control groups performed SEBT with no taping, sham taping, and femoral rotational taping. Main Outcome Measures: The maximum anterior excursion distance, 3-dimensional hip and knee kinematics of the stance leg, and pain score (VAS) during SEBT were recorded. The coefficients of variance (CV) of kinematic data gathered from electromagnetic sensors on pelvis and femur were calculated to represent segmental stability. Results: When performing the SEBT in the anterior direction, application of femoral rotational taping increased maximum excursion distance (65.57% vs 66.15% leg length, P = 0.027), decreased hip adduction excursion (47.6 vs 32.1 degrees, P = 0.010), and pain (3.34 vs 2.38, P = 0.040) in the PFP group. Femoral rotational taping also improved the medial-lateral (7.1 vs 4.6, P = 0.015) and proximal-distal stability (7.5 vs 4.5, P = 0.020) of the pelvis, and medial-lateral stability (7.2 vs 6.1, P = 0.009) of the femur. Conclusions: The results support the use of femoral rotational taping for improving dynamic postural control and reducing pain during SEBT. Clinical Relevance: Femoral rotational taping could be used in the management of young female patients with PFP.